FAN Mothers in Our Fragile Social Network against Climate Change - Duffy, Clare; Hawkes, Jodie; Lovett, Leah; McCloskey, Paula; Šimić, Lena; Svendsen, Zoë; Verson, Jennifer; Townley, Anna (Journal of the Motherhood Initiative for Research and Community Involvement, 2021)
This email chain conversation between eight mother-artist activists written over a period of one year between January 2018 and January 2019 reflects our various family lives and attitudes to climate change at that time. The authors identify as belonging to the Family Activist Network and, consequently, to the environmental movement in the age of the Anthropocene. The piece addresses: (1) the many contradictions, paradoxes, hypocrisies, and incongruences inherent in trying to be mother-artist activists; (2) feminist solidarity; (3) questioning if it is possible to reconcile activism with maternity, under what circumstances, and according to what models of activist/maternal practice; (4) intergenerational injustice; (5) the question of acting or not acting; (6) the question of paying attention—noticing how you live and how you create the conditions for another human to live; (7) other life—other humans, nonhumans, and the earth; and (8) the spectacle of mothers and children in protest— the whole performance of mothering in the public realm, at rallies, marches, and art-activist events.